Human Right and Sustainable Development - Eba, Maxwell-Borjor Achuk (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This work entitled “Human Rights and Sustainable Development” seeks to clarify the phrase ‘sustainability’ as an ethical concept within the framework of human right, and also tend to show that the generally accepted definition is conceptually inadequate. This inadequacy could be seen in the radical differences between various discourses of ‘sustainability’ depending upon the perspective such as social, political, economic, et al. Furthermore, one overreaching concern that requires consideration while dealing with ‘sustainability’ and the ‘environment’ is; ethics. Due to the above, in this work, a theoretical framework will be laid bare wherein it will be argued that all humans have equal rights vis-avis nature and the environment. However, if all humans have equal rights vis-avis nature and the environment, then sustainability must take into account the poor Southern Blocs and their rights to development just like the rich Northern Bloc had done in the past. This work argues that the concept of ‘sustainability’ needs to be revisited. This work also argues that the concept of ‘equal rights’, cannot be justify based on some empirical investigation, but upon moral norm that has its roots in the general theory of ethics; environmental ethics.